Systemic Management of Pandemic Risks in Dental Practice: A Consolidated Framework for COVID-19 Control in Dentistry - Benzian, Habib; Beltrán-Aguilar, Eugenio; Niederman, Richard (Frontiers in Medicine, 2021)
Dental teams and their workplaces are among the most exposed to airborne and bloodborne infectious agents, and therefore at the forefront of pandemic-related changes to how dental care is organized and provided to patients. The increasing complexity of guidelines makes is challenging for clinicians to navigate the multitude of COVID-19 guidelines issued by different agencies. A comparative analysis of guidance issued for managing COVID-19 in dental settings leading U.S. agencies was conducted, including documents of the Occupational Safety and Health Administration (OSHA), an agency of the U.S. Secretary of Labor, and of the U.S. Centers for Disease Prevention and Control (CDC), an agency of the U.S. Secretary of Health and Human Services. Details of infection control and other risk mitigation measures were reviewed for consistency, overlaps and similarities, then clustered according to thematic areas covering all domains of managing a dental healthcare setting. The analysis revealed five distinct areas of pandemic control, comprising 1) planning and protocols, 2) patient screening, 3) preparation of facilities, 4) PPE & infection control, and 5) procedures and aerosol control; thereby covering systematically all aspects requiring adaptation in a pandemic context. The “Pandemic-5 Framework for COVID-19 Control in Dentistry” provides an opportunity to simplify comprehensive decision-making from a clinical practitioner perspective. The framework supports a comprehensive systems-driven approach by using dental clinics as a setting to integrate pandemic clinical responses with the implementation of appropriate infection control protocols. Traditionally these two aspects are addressed independently from each other in separate concepts.